The Science Behind Traditional Products: The Case of Portuguese Cheeses - Guiné, Raquel (2019)
Portugal is situated in the Iberian Peninsula, having climacteric influences of the Atlantic Ocean together with the Mediterranean Sea, which, allied to the landscape and fertile soil results in good pastures that potentiate the animal production. Hence, Portugal is very rich in what concerns traditional cheeses, made with cow, goat, sheep or mixture milks, and which are characterized by very particular tastes, colours and consistencies, besides being also different in terms of chemical composition. The number of Portuguese traditional cheeses is very high, although only a part of them have already been registered under the European Union designations for protection of origin. These have different processing technologies and are characterized by singular aspects that differentiate among them. In this way, they can be classified in terms of the type of milk used for its production, or in terms of the fat content, or even the type and intensity of ripening or finally according to the consistency of the paste. Traditional cheeses are very important in social terms, because they accumulate the history of a people and a country, besides providing a means of income for the rural populations that live from the pastures and the cheese manufacture. Cheeses comprise nutritional properties for being a good source of proteins, lipids, minerals (such as calcium, phosphorus and zinc) and vitamins (like vitamin A, riboflavin, folic acid and vitamin B12). Nevertheless, when it comes to traditional cheeses, they have to be consumed with moderation due to the high fat content present because they are usually made with whole milk.